2021
DOI: 10.3389/fmicb.2021.736407
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic Community Succession in Bulk and Rhizosphere Soils Along a High-Elevation Glacier Retreat Chronosequence on the Tibetan Plateau

Abstract: Early colonization and succession of soil microbial communities are essential for soil development and nutrient accumulation. Herein we focused on the changes in pioneer prokaryotic communities in rhizosphere and bulk soils along the high-elevation glacier retreat chronosequence, the northern Himalayas, Tibetan Plateau. Rhizosphere soils showed substantially higher levels of total organic carbon, total nitrogen, ammonium, and nitrate than bulk soils. The dominant prokaryotes were Proteobacteria, Actinobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In this study, the taxonomic analysis showed that Methylobacterium belonging to Actinobacteria and Pseudarthrobacter belonging to Proteobacteria phyla were the predominant genera at HT and LT, respectively ( Figure 3 c,d). Methylobacterium and Pseudarthrobacter species can fix nitrogen through denitrification [ 52 ]. Enhanced nitrogen fixation may lead to nitrogen accumulation in a cold ecosystem, which promotes microbial growth at a later stage [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the taxonomic analysis showed that Methylobacterium belonging to Actinobacteria and Pseudarthrobacter belonging to Proteobacteria phyla were the predominant genera at HT and LT, respectively ( Figure 3 c,d). Methylobacterium and Pseudarthrobacter species can fix nitrogen through denitrification [ 52 ]. Enhanced nitrogen fixation may lead to nitrogen accumulation in a cold ecosystem, which promotes microbial growth at a later stage [ 22 ].…”
Section: Discussionmentioning
confidence: 99%